Find-Natech: A GIS-based spatial management system for Natech events. (15th June 2022) - Luo, Xiaolong; Tzioutzios, Dimitrios; Tong, Zhijun; Cruz, Ana Maria
Abstract: Technological accidents triggered by natural hazards are considered as Natech events. Natech events involve chemical releases, which could cause serious health and environmental problems and large economic losses. Several studies have pointed out that the number of Natech events is on the rise. Learning lessons from Natech event data could provide critical ideas to risk managers and local governments to take action towards Natech risk reduction. However, there are currently only limited efforts to collect and analyze Natech event data, and especially there are no tools to manage historical Natech data from spatial perspective. This study proposes and develops of a web-based Geographic Information System (GIS) tool, Find-Natech, to collect, analyze and share historical data of Natech events. It presents a case study on analyzing the temporal-spatial distribution of hurricane-related Natech events in the United States based on data from the National Response Center (NRC) database. Furthermore, the case study shows that Find-Natech can support risk managers in understanding the geographical distribution of historical events, their spatial variation by changing over time which could be further used to understand the characterization of Natech events. In addition, the proposed tool can support conducting studies on understanding incidence of Natech events during natural hazards with scale effects at city, state, or national levels, to support risk governance and risk reduction strategies.